2x + 3y = 6

3y = - 2x + 6

y = - 2/3 x + 6/3

y = - 2/3 x + 2

Now from above

Slope = - 2/3

Now the slope of the perpendicular line is

Slope = - 1 / (- 2/3)

= 1 / (2/3)

= 3/2

Now the equation of perpendicular line from points (-3, 2) is

y - (2) = 3/2 (x - (-3))

y - 2 = 3/2 (x + 3)

2y - 4 = 3(x + 3)

2y - 4 = 3x + 9

3x - 2y = - 4 - 9

3x - 2y = - 13 ...........Ans

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up